Flavonoid Extraction from Mango Peels for Nanoparticles by Green Synthesis Process - Supamas Wirunchit; Natchayaporn Sakulpeeb; Sutee Chutipaijit; Jiti Nukaew; Wantana Koetniyom (Current Applied Science and Technology, 2025)
This research study explored the extraction of flavonoids from ripe and raw mango peels using different solvents (deionized water, methyl alcohol, and ethyl alcohol) over varying durations. The extracted compounds were then employed in synthesizing titanium dioxide nanoparticles (TiO2 NPs) via a green chemical process using titanium isopropoxide. Optimal extraction, yielding the highest flavonoid content, was achieved with deionized water after 3 h for ripe peels and 4 h for raw peels. The titanium dioxide nanoparticles synthesized exhibited an anatase crystal structure, as confirmed by XRD, Raman, and FTIR techniques. SEM images showed that the nanoparticles were evenly distributed and had a smooth surface. The titanium dioxide nanoparticles demonstrated stronger antibacterial activity against Escherichia coli than Staphylococcus aureus. Furthermore, raw mangoes were found to be more effective in inhibiting bacterial growth than ripe mangoes.
Keywords: Consumer Packaging Perceptions and Trends